Localization of vitellogenin and serum albumin in hepatic parenchymal cells of normal and estradiol-treated immature chickens - Wachsmuth, Ernst Dieter; Jost, Jean-Pierre (Biochimica et biophysica acta, 1976)
The localization of albumin and vitellogenin was determined in liver sections from control and estradiol-treated chickens by two different immunocytochemical techniques: (1) The sandwich technique with rabbit anti-lipovitellin or rabbit anti-albumin IgG and fluorescent goat anti-rabbit IgG and (2) the mixed aggregation immunocytochemical technique with anti-lipovitellin IgG and fluorescent lipovitellin. The results show that the antibody against albumin bound only to all liver parenchymal cells. Furthermore, the fluorescence intensity was equally strong in the portal, intermediate and central zones of the lobules. The fluorescent stain for vittelogenin was not above background in livers of control chicks but was far above background in estradiol-treated chicks. As with albumin the fluorescent stain was distributed equally among the parenchymal cells. The results were quantitatively the same 2 and 4 days after estradiol treatment. The relative rates of synthesis and the concentrations of albumin and vitellogenin correlate well with values obtained for tissue sections by immunocytochemical techniques.